Selective Sorption of Chromium from Tannery Wastes by Hybrid Cation Exchange Resin - Ahmad, Tauqeer; Mustafa, Syed; Naeem, Abdul; Anwar, Farooq; Hussain Shah, Khizar; Mehmood, Tahir (Asian Journal of Chemistry, 2014)
A hybrid cation exchanger of a strong acid exchanger Amberlite IR-120 with iron hydroxide is used for the removal of chromium(III) from the tannery wastes. The hybrid ion exchanger has been found to have higher sorption capacity for the chromium(III) ions as compared to Amberlite IR-120 and iron hydroxide which is further enhanced with the increase in temperature. Chromium speciation analyses indicate that the main chromium species being sorbed are CrSO4+ and Cr3+, as they are the dominant species present in spent tannery bath solution. The higher sorption by the hybrid ion exchanger is due to the presence of two different types of the sites -SO3H and -OH, and also due to the Donnan sorption effect of the polystyrene anions. The Langmuir sorption isotherm is found applicable to the experimental data. Isosteric heats of adsorption are found to be positive and smaller than 80 kJ mol-1 indicating that the sorption process is endothermic and ion exchange in nature.